PENINGKATAN HASIL BELAJAR PPKN MELALUI MODEL PEMBELAJARAN COOPERATIVE SCRIPT DI SMP NEGERI 1 JOGONALAN, KLATEN - Purwo Haryono; Tukiyo; Sri Suwartini (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article is derived from research about low students’ learning outcomes. The purpose of the research is to determine the cooperative script learning model to improve the learning outcomes of Civic Education learning subject in the state institutions at SMP Negeri 1 Jogonalan Klaten. The type of research used was Classroom Action Research (CAR) with datacollection techniques through learning outcomes tests. The subjects of the research involved 32 students of class IXA SMP Negeri 1 Jogonalan Klaten in the academic year 2021/2022. The results indicated that the cooperative script model could improve the learning outcomes of PPKN learning subjects for class IXA students. The improvement could be seen in the student’s average score in cycle 1 was 65 and in cycle II it was 84. The average score between cycles I and II was 75 in which the percentages of students’ learning completeness from cycle I to cycle II were 69%, 78%, 97%, and 12%. Students learning outcomes could be improved by the way students make and develop the videos, design their own creativity, guide exploration activities, and do motivating exercises.